2019
DOI: 10.1177/0954407018821556
|View full text |Cite
|
Sign up to set email alerts
|

Robust kinematics design of MacPherson suspension based on a double-loop multi-objective particle swarm optimization algorithm

Abstract: In the traditional design of a vehicle suspension system, mechanical parameters, such as spring stiffness and tire radial stiffness, are determined before optimizing the coordinates of suspension hard-points based on handling and stability. However, the mechanical parameters of vehicle suspension systems vary with repeated changes in ambient temperature and loading conditions. Consequently, the original hard-point coordinates cannot guarantee satisfactory handling and stability after long-term vehicle use. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…(21) exist and are unique: (22) x = A (1) b + I n − A (1) A y. (23) x = A (1,4) b, (24) x = A (1,3) b. (25) x = A + b, A (1,3) ∈ A{1, 3}.…”
Section: Algorithm For the Least-squares Generalized Inverse Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…(21) exist and are unique: (22) x = A (1) b + I n − A (1) A y. (23) x = A (1,4) b, (24) x = A (1,3) b. (25) x = A + b, A (1,3) ∈ A{1, 3}.…”
Section: Algorithm For the Least-squares Generalized Inverse Intervalmentioning
confidence: 99%
“…It is relatively easy to ensure the performance of a car; however, ensuring that all cars are simultaneously near the ideal target value is difficult, and there are no particularly stringent requirements for part manufacturing, which is a major challenge for automotive design and performance engineers. At present, multi-objective optimization software [2][3][4][5][6], such as Isight, is used in the industry. The performance of the target vehicle is satisfied by optimizing the sensitive parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension system of a modern vehicle largely reduces the forces, reaction forces and vibrations transmitted to the car body from the road [24][25]. The issue of changes in the wheel geometry, depending on the load, was discussed in [26][27]. It was found that in the suspension systems with a simpler and less complex design (e.g.…”
Section: Issn 1335-4205 (Print Version) Issn 2585-7878 (Online Version)mentioning
confidence: 99%
“…A decrease in the load value influencing the vehicle body and improvement in the vehicle steering properties stems from the structure of the suspension system and the steering system. In [15] it was noted that the driveability and stability of a vehicle may change depending on the stiffness and resilience of the suspension system. On the other hand, the parameters of the suspension system while travelling are influenced by ambient temperature, type of tyres, tyre pressure and vehicle load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the parameters of the suspension system while travelling are influenced by ambient temperature, type of tyres, tyre pressure and vehicle load conditions. Thus, the initial parameters of the shock absorbers operation do not guarantee proper driveability of a vehicle when used under varied load conditions and varied environmental conditions [5,15]. Keeping all components in the right technical condition may provide the user with improved safety [8].…”
Section: Introductionmentioning
confidence: 99%